2022
DOI: 10.1167/tvst.11.5.18
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Validation of In Vitro and In Vivo Models to Investigate TNF-α-Induced Inflammation in Retinal Diseases

Abstract: Purpose Inflammation is implicated in the etiology of diverse retinopathies including uveitis, age-related macular degeneration or diabetic retinopathy. Tumor necrosis factor alpha (TNF-α) is a well-known proinflammatory cytokine that is described as a biomarker for inflammation in diverse retinopathies and therefore emerged as an interesting target to treat inflammation in the eye by neutralizing anti-TNF-α antibodies. Methods Recently, we have demonstrated that Adeno-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…4b). To validate our results, we measured C3 expression by ELISA in an independent mouse cohort 57 and verified the upregulation of also C3 protein at 6 weeks after AAV-TNF-α treatment (Fig. 4c).…”
Section: Aav-tnf-α Mice Show Strong Activation Of Complement Pathway ...supporting
confidence: 59%
See 1 more Smart Citation
“…4b). To validate our results, we measured C3 expression by ELISA in an independent mouse cohort 57 and verified the upregulation of also C3 protein at 6 weeks after AAV-TNF-α treatment (Fig. 4c).…”
Section: Aav-tnf-α Mice Show Strong Activation Of Complement Pathway ...supporting
confidence: 59%
“…Tissue lysis and ELISA. Eyes for validation of C3 expression were generated from an independent mouse cohort that is published elsewhere 57 . In brief, 2 weeks after IVT injection of AAV-TNF-α, 100 µg golimumab (Simponi) were injected intravitreally.…”
Section: Rna Extraction and Quality Control (Aav Study)mentioning
confidence: 99%
“…Following injection, constitutive secretion of IL-23 led to rapid onset of inflammation, followed by a chronic and persistent disease phenotype not observed or attributed to ShH10_GFP response. Use of AAV to model, probe and evaluate therapeutics for human inflammatory ocular disease is an expanding area [81, 82], and in the current context provides a tool to interrogate pathogenicity of IL-23 alone in a disease that is accom-panied by elevated concentrations of serum and AqH IL-23 [39, 41, 42, 83].…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that [54] the expression of TNF-α mRNA was signi cantly increased in diabetic rats induced by a single intraperitoneal injection of 60 mg/kg STZ. A research has demonstrated that [55] Adeno-associated virus (AAV)-mediated expression of human TNF-α in the murine eye induces retinal in ammation. More importantly, TNF-α released from the activated microglia induced BRB damage, which in turn leaded to in ammation of the retinal [56].…”
Section: Construction Of Ppi Network and Molecular Dockingmentioning
confidence: 99%